Tracking of cereal cyst nematode resistance genes in wheat using diagnostic markers - Sharma, Pradeep; Saini, Manoj; Gupta, Om Prakash; Gupta, Nupur; Singh, Arun Kumar; Selvakumar, Rajan; Tiwari, Vinod; Sharma, Indu (Journal of Cereal Research, 2013)
Cereal cyst nematode (CCN), Heterodera avenae, has been reported throughout the world causing reduction in yield of wheat. The major focus of this study was to screen wheat accessions using diagnostic markers for resistance genes to identify the genes for resistance against CCN infestation and aid in the development of the resistant cultivars of bread wheat. Two PCR based co-dominant markers tightly linked to Cre3 and Cre5 resistance genes against CCN were used in this study to screen advanced lines from India and two international nurseries. Inthis study, only RAJ 1 was found positive for presence of Cre3 and Cre5 genes.